Using Synthetic CT for Partial Brain Radiation Therapy: Impact on Image Guidance - Morris, Eric D. (Pract Radiat Oncol, 2018)
PURPOSE: Recent advancements in synthetic computed tomography (synCTs) from MRI data have made MR-only treatment planning feasible in brain, although synCT performance for IGRT is not well understood. This work compares geometric equivalence of digitally reconstructed radiographs (DRRs) from CTs and synCTs for brain cancer patients and quantifies performance for partial brain IGRT. METHODS: Ten brain cancer patients (12 lesions, 7 post-surgical) underwent MR-SIM and CT-SIM. SynCTs were generated by combining ultra-short echo time, T1, T2, and FLAIR datasets using voxel-based weighted summation. SynCT and CT DRRs were compared using patient-specific thresholding and assessed via overlap index (OI), Dice similarity coefficient (DSC), and Jaccard index (JI). Planar IGRT images for 22 fractions were evaluated to quantify differences between CT-generated DRRs and synCT-generated DRRs in 6 quadrants. Previously validated software was implemented to perform 2D-2D rigid registrations using normalized mutual information (NMI). Absolute (planar image/DRR registration) and relative (differences between synCT and CT DRR registrations) shifts were calculated for each axis and 3D vector difference. 1490 rigid registrations were assessed. RESULTS: DRR agreements in anterior-posterior and lateral views for OI, DSC, and JI were >0.95. NMI results were equivalent in 75% of quadrants. Rotational registration results were negligible (<0.07°). Statistically significant differences between CT and synCT registrations were observed in 9/18 matched quadrants/axes (p<0.05). The population average absolute shifts were 0.77 ± 0.58 mm and 0.76 ± 0.59 mm for CT and synCT, respectively for all axes/quadrants. 3D vectors were <2 mm in 77.7 ± 10.8% and 76.5 ± 7.2% of CT and synCT registrations, respectively. SynCT DRRs were sensitive in post-surgical cases (vector displacements >2 mm in affected quadrants). CONCLUSION: DRR synCT geometry was robust. Although statistically significant differences were observed between CT and synCT registrations, results were not clinically significant. Future work will address synCT generation in post-surgical settings.